Preclinical evidence of probiotics in ulcerative colitis: a systematic review and network meta-analysis - Jin, Wenqin; Ai, Huangping; Huang, Qingqing; Li, Chuncai; He, Xiang; Jin, Zhao; Zuo, Yuling (Frontiers in Pharmacology, 2023)
Background: The treatment of ulcerative colitis with probiotics has become a new trend, but the effect of different strains is still controversial. This paper compares different strains through network meta-analysis to provide preclinical evidence for the selection of clinical probiotic strains. Methods: We searched Pubmed, Embase and Web of science for animal experiments on the treatment of ulcerative colitis with probiotics before November 16th, 2022, and two researchers independently conducted literature screening and data extraction. The main outcome were: Weight change (WC), Colon lenth (CL), Disease activity index (DAI), and Historical score (HIS); The secondary outcome were tumor necrosis factor-α (TNF-α), zonula occlusion ns-1 (ZO-1), and Shannon. We used SYRCLE risk of bias assessment tool to evaluate the quality of the included studies. Results: This study included 42 studies, 839 UC models, involving 24 probiotics. Network meta-analysis showed that L. rhamnosus had the best effect in relieving weight loss and increasing Shannon index of UC model. E. faecium had the best effect in reducing colon injury; L. reuteri had the best effect in reducing DAI; L. acidophilus had the best effect in reducing HIS index and increasing the expression of tight junction protein ZO-1; L. coryniformis had the best effect in reducing TNF-α in serum. However, there was no statistical difference between L. rhamnosus in increasing Shannon index and L. acidophilus in increasing the expression of tight junction protein ZO-1 compared with the untreated group. Conclusion: In summary, the results of network meta-analysis showed that different probiotics have different effects on UC model, and some probiotics had definite effects on improving the histopathological manifestations and reducing inflammatory reaction of UC. However, considering the limitations of this study, preclinical studies need more large samples, high quality and more reliable and rigorous experimental designs and reports in the future.